Impact of previous abdominal surgery on the outcome of laparoscopy-assisted open appendicovesicostomy (Mitrofanoff) creation in children: a comparative study. Issue 6 (December 2019) - Kim, Jin K.; Chua, Michael E.; Ming, Jessica M.; Farhat, Walid A.; Koyle, Martin A.; Lorenzo, Armando J.
Summary: Introduction and objective: For patients who require self-intermittent catheterization, a continent catheterizable stoma is a viable option. This patient population often has had previous abdominal surgery (PAS), a risk factor for complicated laparoscopic procedures. Therefore, the authors aim to determine whether PAS has an impact on the peri-operative outcomes of the laparoscopic-assisted Mitrofanoff procedure in children. Materials and methods: A research ethics board–approved retrospective review was performed to assess peri-operative outcomes among pediatric patients who underwent laparoscopic-assisted Mitrofanoff procedures in the authors institution from May 2000 to March 2016. Patients with no PAS were compared with those with intraperitoneal PAS. Demographic/baseline characteristics and peri-operative outcomes such as operative time, estimated blood loss, hospital stay, unanticipated additional operations, stomal stenosis, and urinary continence were compared. To ensure there is no confounding based on PAS characteristics, subgroups were created to compare the recency (PAS <1 year ago) and extent (ventriculoperitoneal (VP) shunt vs non-VP shunt PAS) to assess their peri-operative outcomes. Fisher's exact test and Mann–Whitney U test were used to determine statistical significance. Results: Thirty-four patients (15 no PAS and 19 PAS) were included in the analysis. No significant difference in demographics and baseline characteristics was noted between the patient groups. The median age was 6.5 years (interquartile range [IQR] 4.8–14.0) and 9.9 years (4.2–14.3), respectively (NS). Peri-operative outcomes of operative time, estimated blood loss, and hospital stay were similar between the PAS and no PAS groups. There was no statistical difference in complications requiring surgical intervention (n = 3, 20.0%; n = 9, 47.4%). The median follow-up period was 25.9 (IQR 7.7–47.2) months and 28.0 (IQR 13.0–53.0) months, respectively (NS). Patients with VP shunts as their only PAS had higher estimated blood loss compared with no PAS group (50 [IQR 25-150], 25 [IQR 25-50], respectively) but without other differences in peri-operative outcomes. Discussion: Findings support the use of a minimally invasive approach in this patient population as it is feasible, comparable, and safe but with careful consideration for risk factors that may predispose PAS patients to postsurgical complications requiring intervention. Although limited by small sample size, this study provides valuable insight into performing laparoscopic operations in children who have undergone prior surgeries and invites future studies to compare the outcomes between patients undergoing open, pure laparoscopic, and robotic-assisted laparoscopic Mitrofanoff procedures for children with PAS. Conclusion: Laparoscopic-assisted Mitrofanoff creation may be safely performed in children with PAS. Summary Table Comparison of peri-operative outcomes. Summary Table Laparoscopic Mitrofanoff procedure patients (n = 34) No previous abdominal surgery (n = 15) Previous abdominal surgery (n = 19) P- value N (%), median (IQR) N (%), median (IQR) Operative time (min) 267 (255–340) 255 (196–292) 0.256 Estimated blood loss (mL) 25 (25–50) 50 (25–100) 0.089 Conversion to open surgery 0 (0.0) 0 (0.0) – Length of stay (days) 4 (4.0–5.0) 4.0 (3.0–6.0) 0.302 Follow-up (months) 25.9 (7.7–47.2) 28.0 (13.0–53.0) 0.477 Stoma continence 13 (81.3) 17 (89.5) 0.634 Patients with stoma stenosis 2 (13.3) 4 (21.1) 0.672 Patients with complications requiring intervention (Clavien-Dindo classification ≥3 complication) 3 (20.0) 9 (47.4) 0.152 IQR, interquartile range.